ASPEK SOSIAL DAN NILAI PENDIDIKAN KARAKTER NOVEL SKETSA RASA KARYA PIPIET SENJA: KAJIAN SOSIOLOGI SASTRA - Salma Hanifah; Ferdi Arifin (JURNAL BORNEO AKCAYA, 2022)
This study aims to describe the social aspects and values of character education studied by the literature sociology according to Ian Watt in the novel Sketch of Taste by Pipiet Senja. The present research applied a qualitative descriptive method. The data were collected using a non-interaction technique, that is, reviewing documents and archives. This research was conducted in 6 months, from July to December. The present study found out the social aspects in the form of custom, family, work and education and the values of character education in the form of religious values, moral values, independent values, complex work values, creative values, democratic values, communicative values, and curiosity values. It is recommended that the Indonesian language teachers, students and other researchers examine the social and character education values in literary works.